3D numerical modelling of micro-milling process of Ti6Al4V alloy and experimental validation. Issue 3 (3rd July 2017) - Ucun, İrfan; Aslantas, Kubilay; Özkaya, Ekrem; Cicek, Adem
Abstract: In this study, three-dimensional (3D) finite element analysis was carried out for micro milling of Ti-6Al-4V alloy. The Johnson–Cook material model equation was used, by considering the effects of strain, strain rate and temperature on material properties. The simulation for the milling process of Ti-6Al-4V was conducted through DEFORM based on the established 3D finite element modelling. Additionally, a series of micro-milling experiments on Ti-6Al-4V alloy were carried out to validate the simulation results. For this purpose, cutting tests were conducted using uncoated tools at three different feed rates (2, 3 and 4 μm/flute) and two different cutting velocities (15 and 30 m/min). In the numeric analyses, the cutting force, tool stress and chip formation were estimated and the cutting force, and chip shapes compared with the experimental results. The results of this study show that the experimental cutting force values and chip shapes are in harmony with the numerical ones. In addition, it is observed that cutting force and stress values increase in with increasing the feed rate.